Ethiopia’s Growth and Transformation Plan: A CGE Analysis of Alternative Financing Options: Summary of ESSP Working Paper 30 (November 2011) - Engida, Ermias; Tamru, Seneshaw; Tsehaye, Eyasu; Debowicz, Darío; Dorosh, Paul A.; Robinson, Sherman (International Food Policy Research Institute, 2012)
The Growth and Transformation Plan (GTP) has set higher growth and investment targets than those of any of Ethiopia’s earlier national plans and its implementation requires faster growth in total factor productivity and large-scale mobilization of domestic and foreign savings. We analyzed these GTP targets using a CGE (Computable General Equilibrium) model to assess the implications of the plan on macro- and microeconomic variables. We hereby focused on two financing options: increased domestic savings and increased foreign savings.